2004
DOI: 10.1007/s10388-004-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Omental wrapping of esophageal rupture in combination with T-tube drainage

Abstract: Esophageal rupture is a potentially fatal condition. Rapid and correct diagnosis and urgent surgical treatment are mandatory. Various surgical treatment methods have been reported. We introduced a new surgical procedure for treatment of spontaneous esophageal rupture. Upon thoracotomy continuing to laparotomy, a T-tube was inserted into the esophageal lumen through the ruptured site. The ruptured esophageal wall was sutured interruptedly, and the insertion site was covered with the pedicle omental flap. The T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, Ochiai et al reported a new and satisfactory procedure that involved wrapping a rupture of the lower thoracic esophagus with a pedicled omental flap in combination with T-tube drainage [12]. Esophageal leaks at sites The muscle pedicle exposed on the neck area was covered with splitthickness skin graft harvested from the thigh where it is difficult to achieve healing need continuous suction through the T-tube, in addition to wrapping with a well-vascularized muscle flap.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Ochiai et al reported a new and satisfactory procedure that involved wrapping a rupture of the lower thoracic esophagus with a pedicled omental flap in combination with T-tube drainage [12]. Esophageal leaks at sites The muscle pedicle exposed on the neck area was covered with splitthickness skin graft harvested from the thigh where it is difficult to achieve healing need continuous suction through the T-tube, in addition to wrapping with a well-vascularized muscle flap.…”
Section: Discussionmentioning
confidence: 98%
“…Three patients (nos. 3,4,5) with positive SIRS without pleural effusion or empyema were treated only by drainage under general anesthesia. Five patients positive for SIRS with pleural effusion or empyema on admission underwent a one-stage operation, such as primary closure with tube drainage (patient 1) or two-staged operation such as open window thoracostomy at the fi rst stage operation followed by omental patch at second stage (nos.…”
Section: Casesmentioning
confidence: 99%
“…7 Completion of the total synthesis of danshenspiroketallactones 4 and 5 was then achieved via benzylic oxidation of the mixture of 14 and 15. Notably, by employing peroxide 16, 18 the α-alkoxy benzyl carbon could be chemoselectively oxidized in 80% yield, thus providing a mixture of danshenspiroketallactones 4 and 5. Separation of 4 and 5 via silica gel chromatography proved not possible, because epidanshenspiroketallactone 5 was found to undergo rapid isomerization to 4 on silica gel.…”
mentioning
confidence: 99%